PERTUMBUHAN HURUF AL-QURĀN - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2016)
Letter Qur’an is the connotation of the Arabic alphabet. The growth is thought to have come from several sources. So it appears the formulation of the problem of how growth and development of the letters of the Koran. The research approach is through history to find out the technique of writing the letters of the Koran by way of illustration in the literature data inscription. Data collection is the documentary. Analysis of the data by description is data reduction, data presentation, and conclusion. Letter Koran before being lowered there are several kinds of Umm al-Jimal inscription illustrations, nammarah inscription illustrations and hurron inscription illustrations. Growth in the letter of the Qur’an after he was demoted to experience growth can be followed by a description of the following inscription. First, Kufi, with characteristics: type in the letters often extended horizontal, vertical lines tend to be shorter. There is no syakal or point (i'jam). Evolved into the early Kufi, East Kufi and floral Kufi. Second, naskhi, with characteristics: shape upright on the line, fine lines or thin down. While the scratches to the left or the right thickness. High size of letter is the aleph, letter head fa 'and waw hollow. Letter head of 'ain and ghayn solid at the end of the word, not rigid (arch).. Third, Tsulut, with characteristics: shape bending, easily extended or shortened, rounded and vertical line extended. Fourth, Maghribi, with characteristics: a cross Kufi and naskhi, rounded, curved lines, very prominent below the line at the end of the letter, vertical lines tend to be rather short.